Farmakogenomik dalam Pengobatan Presisi: Tinjauan dengan Studi Kasus Clopidogrel dan Tren Masa Depan - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
Pharmacogenomics has emerged as a cornerstone in the development of precision medicine, aiming to tailor drug therapy based on an individual’s genetic profile. By identifying genetic variations that influence drug metabolism, efficacy,and safety, pharmacogenomics paves the way for improved therapeutic outcomes reduced adverse drug reactions. One of the most significant examples in clinical practice is clopidogrel, an antiplatelet agent whose biopharmacologicalactivation depends on the CYP2C19 enzyme. Genetic variations in CYP2C19 significantly affect the clinical effectiveness of clopidogrel and the risk of major cardiovascular events. This article outlines recent developments in the implementationof pharmacogenomics, focusing on the clopidogrel case study, while also exploring other key gene–drug interactions such as codeine/CYP2D6, warfarin/VKORC1, and statin/SLCO1B1. The review also maps future trends in pharmacogenomics,including multiomic integration, preemptive genotyping, AI-based predictive modeling, and the potential for gene-editing interventions such as clustered regularly interspaced short palindromic repeats (CRISPR). Despite significant progress,implementation challenges remain, ranging from cost and healthcare infrastructure to ethical and regulatory dilemmas. This review aims to provide both a conceptual and practical foundation for the development of truly personalized pharmacotherapy in the future.